[Violence in children ; Ifugao of the heart ; Gary V. [videorecording] - Lazaro, Cheche (The Probe Team, 1980)
Talks about covert violence; importance of mother to tongue by the Ifugaos; transformation of Gary Valenciano in the performance of his songs from an ordinary to a Christian one.